HAK ATAS TANAH ADAT DAN PERMASALAHANNYA - WAYAN RESMINI (GANEC SWARA, 2019)
Land for human life contains a multidimensional meaning, both in terms of social, economic, political and sacred aspects. Because it has a multidimensional meaning, unquestionably every person who owns land will defend his land in any way if his rights are violated.     Land disputes are not a new thing happening in the community. But the dimension of disputes is increasingly widespread in the present, including customary land in its development also has a new value, besides as a means of production, also as a means to speculate (economy) that land has become a commodity where economic transactions take place with expectations of margin (financial) trade in exchanged commodities.     Issues of customary land with a formal juridical approach will not achieve effective results. Law not merely customary is expected to overcome land problems that are so complex and too related to the application of existing laws and regulations. This is needed support with various efforts to ensure the fulfillment of the economic rights of the people, so that at least similar demands can be minimized in the future. In addition, a synergy of positive law in the land sector is needed with customary law in the community, namely (1) an objective understanding of State land, communal land and land rights is needed in the context of customary law and positive law. (2) The approach taken is a persuasive-educational approach and not imposing unilateral will. (3) the need for a cultural religious approach, which can be implemented through three (3) leadership elements, namely traditional leaders, religious leaders, and formal leaders who truly understand traditional law and positive law (UUPA and implementing regulations)